Rak z komórek Merkla u chorych po przeszczepieniu nerki - opis przypadków i przegląd piśmiennictwa - Alicja Dębska-Ślizień; Bolesław Rutkowski; Sławomir Lizakowski; Beata Imko-Walczuk; Dorota Jaśkiewicz; Janusz Jaśkiewicz (Termedia Publishing House, 2011)
aggressivetumour of neuroendocrine cell origin. Long-term immunosuppressionis proven to play one of the most significant roles in MCC development.Organ transplant recipients represent an important percentageof patients with Merkel cell cancer. Prognosis in this group is poor,apparently worse than in non-immunosuppressed patients with MCC.Objective. To present differences in Merkel cell carcinoma betweenpatients undergoing immunosuppressive therapy and the general population.Case reports. Case 1. A 69-year-old male patient, who underwent kidneytransplantation, was referred to the Dermatology Department,because of a facial skin tumour. The lesion was surgically removed andMerkel cell carcinoma diagnosis was confirmed histopathologically.The doses of immunosuppressants were decreased and the patient isunder dermatological care with no further progression. Case 2. A 72-year-old female kidney transplant recipient visited a dermatologist,due to a lesion on her forehead. Histopathology test revealed Merkelcell carcinoma. Computed tomography showed metastases in regionallymph nodes and lungs. The patient died six months after occurrenceof the skin lesion. Case 3. A 79-year-old male patient after kidney transplantationwas examined in the Dermatology Department, presentinga tumour on his right nostril. Initially a squamous cell carcinoma wasdiagnosed and he underwent radiotherapy. After 18 months, he wasreadmitted to the hospital, due to a significant lymph node enlargement.Histopathological examination revealed Merkel cell carcinoma.The patient died because of lung metastases.Conclusions. Merkel cell carcinoma presents a much higher incidenceand worse prognosis in organ transplant recipients than in the generalpopulation. Therefore to reduce the significant potential of morbidityand mortality, the search for better methods of prevention is necessary.